Optimization of Coating Process Parameters by Analysis of Target Powder Thickness and Regression Modeling - Tomislav Šolić; Dejan Marić; Ivan Peko; Ivan Samardžić (Applied Sciences)
The development of corrosion mechanisms is a major issue that industrial experts are faced with while dealing with all phases of metal exploitation. Damage caused by corrosion affects the increase in both direct and indirect costs of manufacture. With adequate surface protection technology, it is possible to lessen the intensity of corrosion mechanisms’ development. In order for the selected surface protection technology to provide its full protective action, it is necessary to be familiar with its process parameters. This paper deals with a surface protection system that creates a barrier between the aggressive environment and the base material. The tested barrier was created on a base material surface by electrostatic powder spraying. In this experiment, three types of base material (carbon steel, aluminum and galvanized steel) were coated by applying different combinations of operating parameters. Operating parameters, i.e., the voltage and strength of the electric current, were taken as numerical input variables in the experiment. Each experiment design was focused on measuring the thickness of the protective layer. Analysis of the obtained results and statistical data processing confirmed that appropriate parameters (input variables) provided the target thickness of the protective coating on each of the tested materials. Optimization of parameters contributes to the efficiency of production, shortens the processing time and ensures that coating thickness stays within the limits defined either by the manufacturer or the end user.